Respiratory effects in the aftermath of a major fire in a chemical waste depot - Greven, Frans; Kerstjens, Huib AM; Duijm, Frans; Eppinga, Pier; de Meer, Gea; Heederik, Dick (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'The aim of this study was to investigate respiratory effects among emergency services first responders and residents with exposure to combustion products in the aftermath of a chemical waste depot fire. ' ' METHODS ': 'The study population comprised 138 individuals who were present in the area downwind of an accidental fire. Identified by telephone interview six years later, subjects with persistent respiratory symptoms were suspected as having Reactive Airways Dysfunction Syndrome (RADS). Medical tests were performed. For bronchial responsiveness, a cut-off point of PD20<2.39 mg histamine was taken and a dose-response slope (DRS) was calculated. Suspected RADS cases were compared with healthy controls for exposure to combustion products, lung function, and bronchial responsiveness. ' ' RESULTS ': 'The 25 suspected RADS cases were more frequently exposed than the 99 controls; the crude odds ratio for high versus low exposure was 6.5 [95% confidence interval (95% CI) 2.4–18.0]. Suspected cases showed a lower ratio of forced expiratory volume in one second to forced vital capacity (FEV1/FVC; P=0.028). Overall, suspected cases had higher DRS than controls. The difference was significant for males only (P=0.006), and non-smoking males (P=0.014). Highly exposed subjects had higher DRS than low exposed subjects (P=0.056). These differences were significant when restricted to non-smokers (P=0.034) and to males (P=0.019). Differences between cases and controls were stronger when the population was restricted to current non-smokers. ' ' CONCLUSIONS ': 'Persistent respiratory symptoms and bronchial responsiveness were associated with exposure to combustion products of a chemical waste depot fire which occurred more than six years earlier. Authorities and emergency services are recommended to take this into consideration when managing incidents in order to limit possible exposure to airway irritants.
Keywords: airway irritant; chemical fire; chemical waste depot; dose-response slope; fire; histamine challenge testing; persistent respiratory symptom; RADS; reactive airways dysfunction syndrome; respiratory effect